SYNERGISTIC EFFECT OF RADIATION AND TRADITIONAL CHINESE MEDICINE RHIZOMA TYPHONII ETHANOL EXTRACTS DEPENDS ON P53 EXPRESSION IN TREATMENT OF LEWIS MOUSE LUNG CANCER CELLS - Zhao, Yinlong; Zhao, Lingjun; Luo, Yunxiao; Li, Xin; Zhang, Yifan; Liu, Xiaodong; Luo, Yungang; Zhong, Lili (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Lung cancer is the leading cause of cancer-related death, and it is the most common cancer in terms of both incidence and mortality. There is an urgent need on novel therapeutic strategies for lung cancer. Traditional Chinese herbal medicines (CHM) have potential valuable for cancer treatment. Materials and Methods: Lewis mouse lung cancer cell line and Lewis cells tumors xenograft were used in this experiment. MTT assay was used to detect cell proliferation, flow cytometry (FCM) analysis and Western blotting to detect cell apoptosis, and colony formation assay to evaluate the effect of combined therapy of RT+IR.Results: Our data showed that Rhizoma typhonii (RT) obviously inhibited the proliferations of Lewis cells in time and dose dependent manners by MTT assay and enhanced radiosensitivity by colony formation assay. The effects of RT to Ionizing radiation (IR) therapy were demonstrated radiosensitivity on tumors xenograft experiment. In our study, RT induced apoptotic in Lewis cells directly and enhanced the pro-apoptotic effect of IR by regulating the expression of p53. Conclusions: These data suggested that RT may be a great potential anti-tumor medicine and the combination of RT and IR may provide a new therapeutic strategy for the treatment of Lewis lung cancer.